2015
DOI: 10.1088/0954-3899/42/7/075106
|View full text |Cite
|
Sign up to set email alerts
|

Realisticαpreformation factors of odd-Aand odd-odd nuclei within the cluster-formation model

Abstract: The recently proposed cluster-formation model (CFM) (Ahmed et al 2013 J. Phys. G: Nucl. Part. Phys. 40 065105) is extended to calculate the α preformation factors of odd-A and odd-odd nuclei. The extraction process of the formation energy of a preformed α cluster is analyzed in detail, which is crucial for determining the realistic α preformation factor in CFM. With an adaptive modification in the formation energy, we investigate the α preformation factors of odd-A and odd-odd heavy nuclei, and our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…The basic assumption in the CFM formalism is that the nucleons around the surface contribute to the preformation of the α-particle. In this model, the α-preformation factor is defined as P α = E f α /E, where E f α is the formation energy of the α-cluster and E is the total energy of a considered system [31,32,33,34,35]. In order to use the accurate mass excess which is vitally important to obtain the precise binding energies, the data are given from [57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic assumption in the CFM formalism is that the nucleons around the surface contribute to the preformation of the α-particle. In this model, the α-preformation factor is defined as P α = E f α /E, where E f α is the formation energy of the α-cluster and E is the total energy of a considered system [31,32,33,34,35]. In order to use the accurate mass excess which is vitally important to obtain the precise binding energies, the data are given from [57].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, cluster formation model (CFM) [31,32,33,34,35] was proposed to extract the α-preformation factor in terms of the α-cluster formation energy based on the binding energy differences of the participating nuclide, which is in good agreement with different microscopical approaches. Deng et al [36] studied the α-decay halflives for nuclei around Z = 82, N = 126 closed shells by the proximity potential 1977 formalism; they confirmed that the effective and microscopic P α within the CFM reduce the discrepancy between theoretical and experimental data in the mentioned region.…”
Section: Introductionmentioning
confidence: 96%
“…The clusterformation model (CFM) is a new quantum mechanical theory was first promoted to calculate the αpreformation factors P α of eveneven nuclei [41,44]. After that, this model was proposed to calculate oddA and oddodd nuclei [40,42,54]. The total state Ψ of the parent nucleus is a linear combination of its n possible clusterization states Ψ i , which can be defined as…”
Section: Cluster-formation Model (Cfm)mentioning
confidence: 99%
“…The problem of the quantum many-body system is complex; hence, the α-preformation factors are obtained from the ratios of calculated to experimental α-decay half-lives [38,39]. The recently proposed cluster formation model [40][41][42][43][44] suggests that the α-preformation factor can be extracted in terms of the α-cluster formation energy based on the binding energy differences of the participating nuclide. Meanwhile, the behavior of Q α and P α values of 118≤Z≤128 isotopes with increasing neutron number N has been systematically studied [20]; In consequence, it is suggested that N=178 may be the neutron magic number.…”
Section: Introductionmentioning
confidence: 99%
“…The ↵ emission is usually explained as the formation of a cluster on the surface of the daughter nucleus followed by a penetrability of an external barrier at an energy close to the Q-value [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The probability to form such a combination is given by a square overlap of the convolution of the wave functions of the parent nucleus and that of the system at the touching configuration.…”
Section: Introductionmentioning
confidence: 99%